Omissions and Deviations From Safe Drug Administration Guidelines in 2 Medical Wards and Risk Factors: Findings From an Observational Study - Savva, Georgios; Merkouris, Anastasios; Charalambous, Andreas; Papastavrou, Evridiki (My University, 2022)
Objectives This study aimed to record the type and frequency of errors, with an emphasis on omissions, during administration of medicines to inpatients and to investigate associated factors. Methods This was a descriptive observational study. The medication process in 2 medical wards was observed by 2 observers using a structured observation form. χ2 Test, Kruskal-Wallis test, and regression analysis were used to explore associations between factors and errors. Results From the 665 administrations observed, a total of 2371 errors were detected from which 81.2% were omissions and 18.8% were errors of commission. Omissions in the infection prevention guidelines (46.6%) and in the 5 rights of medication safety principles (35.8%) were a predominant finding. In particular, omitting to hand wash before administering a drug (98.4%), omitting to disinfect the site of injection (37.7%), and omitting to confirm the patient’s name (74.4%) were the 3 most frequently observed omissions. Documentation errors (13.1%) and administration method errors (4.5%) were also detected. Regression analysis has shown that the therapeutic class of the drug administered and the number of medicines taken per patient were the 2 factors with a statistical significance that increased the risk of a higher number of errors being detected. Conclusions Errors during drug administration are still common in clinical practice, with omissions being the most common type of error. In particular, omissions in the basic infection and safety regulations seem to be a very common problem. The risk of a higher number of errors being made is increased when a cardiovascular drug is administered and when the number of medicines administered per patient is increased.
Keywords: Drug administration; Drug safety; Patient safety; Risk factors